The Role of Audit Opinion in Driving Financial Performance of Provincial Government: Case Study Based on BPK Audit Report - Fahrum Nisa; Silvi Dwi Utari; Dito Aditia Darma Nasution (Yayasan Multidimensi Kreatif, 2025)
This study aims to describe the role of the Supreme Audit Agency (BPK) in preventing state budget deviations through financial audits. This research uses a qualitative descriptive approach with secondary data obtained from the BPK audit report, scientific journals, and relevant policy documents. The findings indicate that financial audits conducted by BPK play an important role in identifying and preventing budget deviations by providing recommendations for improving state financial management. Findings from the BPK audit report, such as discrepancies in the procurement of goods/services and violations of financial regulations, indicate gaps in the budget management system that need to be addressed. The BPK audit functions not only as a detection tool but also as a preventive instrument by creating a deterrent effect and enhancing transparency and accountability in state financial management. This research is expected to provide deeper insights into the importance of the role of financial audits in better budget management.